Aggregating performance measures of a multi-echelon supply chain using the analytical network and analytical hierarchy process. (2nd June 2010) - Drzymalski, Julie; Odrey, Nicholas G.; Wilson, George R.
Performance measures of a multi-echelon Supply Chain (SC) assist SC Managers in making strategic decisions. The measures associated with an inter-organisational SC are an aggregation of the performance measures of the SC members. However, two types of dependencies exist in a multi-echelon SC: intra- and inter-organisational. The former type accounts for the relationship between various parts or departments of a firm, while the latter accounts for the influence of one organisation upon another. Traditional hierarchical techniques are inaccurate to use as an aggregation method for the performance measures as they do not account for dependency. The level of dependency within and among firms needs to be determined. In this paper, a two-dimensional approach is taken using the analytical hierarchy process with the analytical network process to overcome the deficiency with a hierarchical approach.